Identification of the Subsurface Structure of the Great Sumatra Fault Dikit Segment Based on First Horizontal Derivative (FHD), Second Vertical Derivative (SVD), and Forward Modelling Analyses Forward Modelling of 2D Gravity Anomaly Data - Rinanda, Shelya Trya (Himpunan Ahli Geofisika Indonesia (HAGI), 2024)
The Dikit segment has a length of 66.19067 km, located at coordinates 2.291° - 2.748° N and 101.155° - 101.599° E. This segment shows tectonic activity with a slip rate of 9-11 mm/year. One of the effective Geophysical methods to recognise the presence of faults is the gravity method. The purpose of this study is to determine the distribution pattern of heavy force anomalies and to identify subsurface structures in the Dikit segment area by taking GGMPlus heavy force anomaly data. Based on the Bouguer anomaly value, the high anomaly in this area is controlled by the presence of metamorphic rocks around the study area. Meanwhile, the low Bouguer anomaly is due to the presence of a weak zone around the Gunung Masurai area triggered by geothermal activity in the area. The separation of regional and residual anomalies uses a moving average by taking the average value of the cut-off wave number from the results of the spectrum analysis. Based on the analysis of FHD and SVD values, it has been identified that the Dikit segment has a right strike-slip mechanism that extends from northwest to southeast. Forward modelling was carried out using Grav2DC software to map the subsurface structure in the study area.